A versatile method for the selective core-crosslinking of hyaluronic acid nanogels via ketone-hydrazide chemistry: from chemical characterization to in vivo biodistribution. (14th June 2018) - Garcia, Francielle Pelegrin; Rippe, Marlène; Companhoni, Mychelle V. P.; Stefanello, Talitha Fernandes; Louage, Benoit; Van Herck, Simon; Sancey, Lucie; Coll, Jean-Luc; De Geest, Bruno G.; Vataru Nakamura, Celso; Auzély-Velty, Rachel
Abstract : Nanogels show long in vivo blood circulation time and high tumor accumulation. Abstract : The development of biopolymer-based nanogels has gained particular interest to achieve successful delivery of therapeutics for the treatment of various diseases, such as cancer, infection and diabetes. Herein, we report a new and simple methodology for the covalent stabilization of self-assembled gel nanoparticles based on hyaluronic acid (HA) modified with a thermoresponsive ketone-functional copolymer. This relies on the selective formation of hydrazone crosslinks with bishydrazides within the globular domains of the copolymer chains formed above the cloud point temperature. This approach allows tuning of the crosslinking density by varying the dihydrazide crosslinker to ketone molar ratio. The size distributions and morphology of the nanogels were assessed using dynamic light scattering (DLS), cryo-transmission and scanning electron microscopy. In vitro cellular uptake in several cancer cells and in vivo biodistribution of the nanogels in different mouse tumor models were then explored to assess the effectiveness of this crosslinking strategy. The data from these experiments show prolonged blood circulation, longer than 24 hours, for the crosslinked nanogels and high tumor accumulation.